Joint sounds in complete denture wearers. Literature review. - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Monteiro, Douglas Roberto (My University, 2010)
Long-term denture wearers can present with prosthesis instability, reduced occlusal vertical dimension and incorrect positioning of the jaw. This can lead to muscular changes and joint vibration. This study presents the main considerations related to joint vibrations in partially or totally edentulous patients. Occlusal treatment improves the disc-condyle relationship in the mandibular fossa. Furthermore, a detailed clinical exam and anamnesis must be performed to identify the dysfunction and its etiology, so that appropriate treatment can be provided.
Keywords: auscultation; denture; human; mouth disease; myofascial pain; pathophysiology; review; sound; temporomandibular joint; tooth occlusion; vibration; Auscultation; Denture, Complete; Humans; Mouth, Edentulous; Sound; Temporomandibular Joint; Temporomandibular Joint Dysfunction Syndrome; Vertical Dimension; Vibration